Fugere urbem et locus amoenus quaerere: uma análise ecocrítica de Marcovaldo ou As estações na cidade, de Italo Calvino - Marino, Mariana Cristina Pinto (2018)
The present research proposed the analysis of all twenty short stories that compose the book Marcovaldo or the seasons in the city (2015 [1963]), by Italo Calvino. The analyses focused on the protagonist, Marcovaldo, an impoverished proletarian that finds himself in a continuous state of discomfort with the changes that occurred in the post-war social context, especially in Italy during the period of the economic miracle, which was driven by the end of protectionist measures in the economy (GINSBORG, 2003). In trying to break away from this scenario, seeking the genuine beauty of nature, Marcovaldo ends up experiencing situations that always lead him to a discontent that is inextricably linked to a new kind of human and social relationship, built not only on the consolidation of modern capitalist societies, but also on the imposition of a single standard of behavior on society – an anthropological mutation, as proposed by Pier Paolo Pasolini (1978, 1997). The research focused on the Ecocritical approach (GARRARD, 2006), awakened by the object, which suggests the study (incorporating references from areas such as Sociology, Biology and Anthropology to Literary Theory) of nature, its relationship with women and men, and the refining of perceptions about delicate ecological issues, captured more intensively since the 1960s (PIGA, MANSANO, 2015), although the changes in perspective on sensitivity to nature are constantly shifting, mainly since the Enlightenment (THOMAS, 2010 [1983]). This research also integrated the assumptions of Ecosophy (GUATTARI, 2006 [1989]), which suggests a re-signifying of hegemonic procedures and discourses derived from the capitalist socio-political-economic system. In order to do so, it was necessary, jointly, to understand issues related to the environmental context of the twentieth century and its impact on economically disadvantaged classes (BOFF, 1995), as well as to assimilate the consequences related to the environmentalism of the poor, advocated by Joan Martínez Alier (2014 [2007]), in view of the social class to which Marcovaldo belongs. Based on the principles described, this research therefore had to analyze the interactions of Marcovaldo and his family with nature and its possibilities, its modifications and assimilation into an effervescent consumer market, aiming to reflect on the ecological crisis (of the three ecologies, according to Guattari) and point out hypotheses of overcoming it, by means of the apology of a less predatory human conviviality in relation to the other beings that, with them, live on planet Earth.